Algirdas Julius Greimas: Education, Convictions, Career - Broden, Thomas F. (Colloquia, 2014)
The publications that Algirdas Julius Greimas (1917–1992) produced from 1943 to 1992 provide a record of his ideas, opinions, and scholarly methodologies. Yet we have much less information and understanding of his early years. This article draws from archival documents, correspondence, published sources, and personal interviews with Greimas and others to describe the formative experiences inside and outside the classroom which had the greatest impact on fashioning his subsequent life of ideas.The essay describes the linguistic and cultural context in which Greimas grew up, indicates the intellectual traditions in which he was trained, and highlights the individuals, methods, authors, and books of his youth which proved particularly significant for him. A narrative relates his education in Lithuania, describes his university studies in 1930s France, and concludes at a time when much of Europe was engulfed in World War II. A discussion then synthesizes the experiences recounted and explores the ways in which they informed the ensuing evolution of his outlook, ideas, and career.Four traditions played a leading role in shaping Greimas’ s development. Lithuania fashioned his character and identity, afforded him a sound humanistic education, inculcated in him traditional European folklore and a poetical spirit, and instilled in him the commitment to help build the nation’s culture and society. The Slavic heritage provided him metaphysical perspectives, exemplified a holistic approach to inquiry, and developed his revolutionary spirit. Germanic cultures furnished him historical perspectives and methodologies, engaged him in fundamental philosophical inquiry, and provided him a method and an ethic for research on language. France inspired in him a second identity, cultivated in him classical and Enlightenment ideals, and moved him with pure poetry. The various traditions nurtured in Greimas productive tensions between fidelity and openness, historicity and universality, and between reason, affect, and sensuality.
Keywords: biography; historiography; linguistics; philology; Wörter und Sachen; semiotics; intellectual traditions; Catholicism; Existentialism; poetry; modernism